Epidemiology and injury trends in the National Basketball Association: Pre- and per-COVID-19 (2017-2021) - Torres-Ronda, L.; Gámez, I.; Robertson, S.; Fernández, J. (PLOS ONE, 2022)
Purpose: The aim this study was to provide an epidemiological injury analysis of the National Basketball Association, detailing aspects such as frequency rate, characteristics and impact on performance (missed games), including COVID-19 related and non-related injuries. Methods: A retrospective study was conducted from the 2017-18 to 2020-2021 season. Publicly available records from the official website of the National Basketball Association were collected, including player`s profiling data, minutes played per game until the injury occurred, unique injuries and injury description [location (body area), diagnosis (or mechanism)], and missed games due to injury. Results: A total of 625 players and 3543 unique injuries were registered during the period analyzed. There was an increased incidence of missed games and unique injuries ratios, from 2017-18 until 2020-21, even when excluding COVID-19 related cases. The main body areas of injuries corresponded to lower body injuries, specifically knee, ankle and foot. The tendon/ligament group, for both games missed and unique injuries, showed the higher ratios (1.16 and 0.21, respectively), followed by muscle (0.69 and 0.16, respectively) and bones (0.30 and 0.03, respectively). Irrespective of season, the higher percentage of unique injuries occurred in the group of players playing in the 26-35 minutes, followed by the 16-25 minutes played. Guards showed the highest injury ratios compared to other playing positions. Most injuries and missed games due to injury occurred from mid-season to the end of the regular season. The majority of both injuries and missed games were concentrated in the two central experience groups (from 6 to 15 years). Conclusions: Despite previous efforts to better understand injury risk factors, there has been an increase in unique injuries and missed games. The distribution by body area, type of injury, when they occurred, minutes played and outcomes by play position, age a or years of experience vary between season and franchises.